A theory of justice in its natural and political states, according to Hobbes - Aranda Fraga, Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Contractualism explains and accounts for the foundation and the possibility of society as stemming from an agreement between free and equal beings. According to Hobbes, before agreeing to it, men used to live in a state of war against each other with no room for justice. There were no laws either, nor property nor any kind of civilization. In short, there were no rights, and therefore it became essential to look for an efficient solution. Then it was decided -out of a mutual agreement- to appoint a guarantor of their rights and duties; thus, the State is born and only from then on justice is established.